The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fpsyg.2022.916980
|View full text |Cite
|
Sign up to set email alerts
|

An ecological approach to understanding university English teachers’ professional agency in implementing formative assessment

Abstract: As a sub-realm of Language Teacher Psychology (LTP), teachers’ professional agency has gained significant attention from educational practitioners and teachers. The aim is to better discern teachers’ professional development and teaching effectiveness with a view to ensuring the quality of language teaching. International literature concerning teachers’ professional agency has noted a shift from knowledge training to vocational development in relation to teachers’ experience in decision making. Yet, little res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…The study by Jiang et al (2022) also found that teachers recognized the value of formative assessment activities in developing student learning and enhancing their own teaching capacity, which underscored the importance of promoting and facilitating professional agency for sustainability in the teaching context. Figure 2 highlights the interrelated dimensions that enabled teachers to exercise their professional agency in the formative assessment process (Jiang et al, 2022).…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…The study by Jiang et al (2022) also found that teachers recognized the value of formative assessment activities in developing student learning and enhancing their own teaching capacity, which underscored the importance of promoting and facilitating professional agency for sustainability in the teaching context. Figure 2 highlights the interrelated dimensions that enabled teachers to exercise their professional agency in the formative assessment process (Jiang et al, 2022).…”
Section: Introductionmentioning
confidence: 89%
“…The study highlighted the importance of teachers analyzing their experiences from a Fig. 2 A framework of teachers' professional agency in formative assessment implementation (Jiang et al, 2022) critical perspective, their awareness of present opportunities, and future aspirations in enacting teacher agency in assessment. However, teachers faced challenges in negotiating their agency within the existing environmental conditions, leading to struggles and the need for ecological transformation.…”
Section: Introductionmentioning
confidence: 99%
“…Essentially, formative assessment evaluates students' daily learning processes, achievements, and the dynamic aspects of their emotions, attitudes, and strategies. It revolves around a comprehensive assessment of the entire student learning journey through continuous observation, recording, and reflection, with the primary goal of inspiring active student engagement, effective self-regulation, and the development of a sense of accomplishment, selfconfidence, and a collaborative spirit [10].…”
Section: Teaching Formative Assessmentmentioning
confidence: 99%